Museum collections management : a handbook - Matassa, Freda (London : Facet Publishing, 2011)
'Collections Management is a relatively new term in museums, and yet it is fundamental to what museums do and why they exist. To collect, display, care for and access museum objects, was and remains the core purpose of our museums and galleries. Recently the term has come to be synonymous with database systems to store and generate information on collections, but in its wider sense, it encompasses all the activities of those engaged in caring for our national heritage. The purpose of this book is to answer all questions from what is collections management and why it is important, to how to classify objects or draw up a contract for a shared acquisition. As such, this is the first publication of its kind to act as a comprehensive and practical guide to collections management.'--Publisher.
Includes bibliographical references (p. 245-250) and index.
Keywords: Museums -- Collection management -- Handbooks, manuals, etc; Museum techniques -- Handbooks, manuals, etc